Prevention or inhibition of foam formation through identification of non-existence domains in the interface in random and structured column-packings - Almazan Torres, Lidia; Osorio Nesme, Anuhar; Delgado, Antonio (Proceedings der 27. GALA-Fachtagung "Experimentelle Strömungsmechanik", 2019)
Undesired foams in reactors occupy the place 11 out of 31 of the causes of column malfunctions. These malfunctions are mainly caused by interfering with transport processes and chemical reactions up to the complete disruption of the process. The wide range of consequences (e.g. waste of time, energy, resources, costs …) affect the production of food as well as of fine chemicals. The influence of the shape of both random and structured packings on foam formation located on trays of the packed columns has not been studied as far as we are concerned. The present work aims for a better understanding of the physics behind the foam formation along with its prevention or inhibition, depending on the packing shape. Possible analytical and numerical solutions for laminar fully-developed flows through random or structured packings under the effect of gravity when the packings are located inside packed columns are investigated. As a starting point, a zigzag geometry with an internal angle 2α is chosen. We propose an analytical expression that describes both the fluid behaviour through the chosen geometry and the shape of the interface generated between the liquid and the gas. Relevant parameters such as surface tension and contact angle are considered in the analysi
Keywords: Foam; packings; column